Identifikasi Literasi Informasi Dalam Rangka Pengembangan Kurikulum Di Sekolah Dasar - Ronald Marseno; Wisnu Ananta Kusuma; Abdul Rahman Saleh (Jurnal Pustakawan Indonesia, 2014)
ABSTRACTInformation literacy is defined more than just using technology to obtain information such as the use of internet and e-book, or library user education that have become one of public service in a library. Information literacy skills need to be supported by another skill, one of which is digital literacy skill. This study aimed to identify information literacy skills using information technology and digital literacy skills referring to standard conditions and objectives that have been implemented in learning activities. Descriptive approach which refers to the TRAILS (Tool for Real-time Assessment of Literacy Skills) and  SPCLC digital literacy standards used as a method in this study. We investigated the digital literacy skills and the information literacy skills of students from two elementary school in Jakarta. The result showed that the digital literacy skills of the  students did not affect to their information literacy skills. Therefor, we recommend to conduct curriculum development which integrate information literacy subject in activities of learning by using computer and internet.Keywords : Information literacy, digital literacy, recommendations for curriculum development.